The interaction of focus and phrasing with downstep and post-low-bouncing in Mandarin Chinese - Wang, Bei; Kügler, Frank; Genzel, Susanne (Frontiers in Psychology, 2022)
L(ow) tone in Mandarin Chinese causes both downstep and post-low-bouncing. Downstep refers to the lowering of a H(igh) tone after a L tone, which is usually measured by comparing the H tones in a “H…HLH…H” sentence with a “H…HHH…H” sentence (cross-comparison), investigating whether downstep sets a new pitch register for the scaling of subsequent tones. Post-low-bouncing refers to the raising of a H tone after a focused L tone. The current study investigates how downstep and post-low-bouncing interact with focus and phrasing in Mandarin Chinese. In the experiment, we systematically manipulated (a) the tonal environment by embedding two syllables with either LH or HH tone (syllable X and Y) sentence-medially in the same carrier sentences containing only H tones; (b) boundary strength between X and Y by introducing either a syllable boundary or a phonological phrase boundary; and (c) information structure by either placing a contrastive focus in the HL/HH word (XF), syllable Y (YF), or the sentence-final word (ZF). A wide-focus condition served as the baseline. With systematic control of focus and boundary strength around the L tone, the current study shows that the downstep effect in Mandarin is quite robust, lasting for 3–5 H tones after the L tone, but eventually levelling back again to the register reference line of a H tone. The way how focus and phrasing interact with the downstep effect is unexpected. Firstly, sentence-final focus has no anticipatory effect on shortening the downstep effect; instead, it makes the downstep effect lasts longer as compared to the wide focus condition. Secondly, the downstep effect still shows when the H tone after the L tone is on-focus (YF), in a weaker manner than the wide focus condition, and is overridden by the post-focus-compression. Thirdly, the downstep effect gets greater when the boundary after the L tone is stronger, because the L tone is longer and more likely to be creaky. We further analyzed downstep by measuring the F0 drop between the two H tones surrounding the L tone (sequential-comparison). Comparing it with F0 drop in all-H sentences (i.e., declination), it showed that the downstep effect was much greater and more robust than declination. However, creaky voice in the L tone was not the direct cause of downstep. At last, when the L tone was under focus (XF), it caused a post-low-bouncing effect, which is weakened by a phonological phrase boundary. Altogether, the results showed that although intonation is largely controlled by informative functions, the physical-articulatory controls are relatively persistent, varying within the pitch range of 2.5 semitones. Downstep and post-low-bouncing in Mandarin Chinese thus seem to be mainly due to physical-articulatory movement on varying pitch, with the gradual tonal F0 change meeting the requirement of smooth transition across syllables, and avoiding confusion in informative F0 control.